Hemophagocytic lymphohistiocytosis: a rare and life-threatening diagnosis - Yarky, Anu; Kumar, Vipan; Chauhan, Nidhi; Verma, Neha (International Journal of Research in Medical Sciences, 2021)
Hemophagocytic lymphohistiocytosis (HLH) is a rare and life-threatening syndrome of excessive activation of immune system. It frequently affects infants from birth to 18 months of age, but is also observed in children and adults of all ages. HLH can occur as a familial or sporadic disorder, and it is triggered by a variety of events, Infection being the most common trigger both in familial and in sporadic cases. Prompt treatment is very critical in cases of HLH, but the greatest barrier is often delay in diagnosis due to the rarity of this syndrome, variable clinical presentation, and lack of specificity of the clinical and laboratory findings. The key clinical features of HLH are high persistent fever, hepatosplenomegaly, blood cytopenia, elevated aminotransferase and ferritin levels, and coagulopathy. A diagnosis of HLH is mostly under-recognized, and is associated with high mortality, especially in adults; thus, prompt diagnosis and treatment are essential. We here present a rare case of HLH in an adult which was non-familial and infection being the trigger causing secondary hemophagocytic lymphohistiocytosis.